Knowledge, Attitude, and Practices towards Face Mask usage among Undergraduate Medical and Para-medical Sciences Students: A Cross-Sectional Study - Yap Rui Zheng; Ubaidullah Osman Ahmad Johari; Kharina Haziqa Ahamad Naina; Magdalene Cheryl Mark Clement; Maisara Yusra (Asian Journal of Medicine & Health Sciences, 2022)
Background: A face mask serves the purpose of providing a physical barrier against respiratory infections via respiratory droplets. Recognizing the knowledge, attitude, and practice of university students regarding face mask usage is important to identify gaps and intervene immediately to manage the spread of the infection. Thus, our objective in this study is to identify the knowledge, attitude, and practise of face mask usage and to determine the associated factors of proper practice of face mask usage among the University of Cyberjaya (UoC) medical undergraduate and para-medical sciences students. Methods: One hundred and sixty participants from UoC’s undergraduate programmes in medical and paramedical sciences participated in a cross-sectional survey using an online questionaire from July 2021 to October 2021. The questionnaire used was from a study in Ethiopia which consisted of basic sociodemographic characteristics, and the knowledge, attitude, and practices regarding face mask usage for limiting COVID-19 exposure. A logistic regression model was used to determine the factors associated with the proper practice of face mask usage. Results: The study showed that the percentage of good knowledge, attitude, and practice of the healthcare providers toward proper face mask utilization were 32.5% (n=52), 64.0% (n=103), and 88.1% (n=141) respectively. Factors associated with proper utilization of face masks were age, ethnicity, the field of study, marital status, and good knowledge about face mask use. Conclusion: In our study, majority of the students had poor knowledge however they still possess a good attitude and practice toward face mask usage. We hope that this will prompt the public to increase their knowledge about the proper usage of face masks especially in combating the COVID-19 pandemic.